Studying the Structures of Relaxed and Fuzzy Interactions: The Diverse World of S100 Complexes - Ecsédi, Péter; Gógl, Gergő; Nyitray, László (Frontiers in Molecular Biosciences, 2021)
S100 proteins are non-catalytic small, dimeric, EF-hand Ca2+-binding proteins. Their concentrations are detectably perturbed in cancer growth, metastasis, rheumatic and neurodegenerative diseases. They can control the function of numerous proteins via protein-protein interactions. A good number of these complexes were found to have fuzzy properties. Examining these highly flexible interactions is a difficult task, especially from a structural biology point of view. Here we summarize the suitable in vitro techniques, which could be utilized to gain structural information about these dynamic complexes. We also review what we know about the structures of S100 complexes focusing on their asymmetric nature.